2018
DOI: 10.1111/conl.12573
|View full text |Cite
|
Sign up to set email alerts
|

Generic names and mislabeling conceal high species diversity in global fisheries markets

Abstract: Consumers have the power to influence conservation of marine fishes by selectively purchasing sustainably harvested species. Yet, this power is hindered by vague labeling and seafood fraud, which may mask market biodiversity and lead to inadvertent consumption of threatened species. Here, we investigate the repercussions of such labeling inaccuracies for one of the world's most highly prized families of fishes-the snappers (Family: Lutjanidae). By DNA barcoding 300 "snapper" samples collected from six countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 24 publications
0
33
0
1
Order By: Relevance
“…If mislabeling occurs before landing data is collected, commercial landing data could be artificially inflated for in-demand species, and artificially low for substituted species (Di Pinto et al, 2015a). This could affect management efforts by potentially allowing unregulated overharvesting of substitute species (Carvalho et al, 2011;Cox et al, 2012;Cawthorn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…If mislabeling occurs before landing data is collected, commercial landing data could be artificially inflated for in-demand species, and artificially low for substituted species (Di Pinto et al, 2015a). This could affect management efforts by potentially allowing unregulated overharvesting of substitute species (Carvalho et al, 2011;Cox et al, 2012;Cawthorn et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At the very least, consumers should be empowered to make choices that support sustainable use of natural resources. This is impossible when retailers are permitted to group many species under one label, for example, ‘Snapper’ is an umbrella term that has found to be applied to more than 60 species in 16 fish families (Cawthorn, Baillie & Mariani, 2018). An example in the AFNS is Basa.…”
Section: Discussionmentioning
confidence: 99%
“…This increased interest in food authenticity may also be explained by the numerous food scandals over the last few years (e.g., horsemeat scandal in 2013 and rotten meat from Brazil in 2017) and the increased consumer awareness about the impacts of food fraud in terms of illegal economic gain, as well as negative effects on the public health and the environment. Nonetheless, several recent studies have indicated that fraud or mislabeling is still a widespread practice, especially in food products of animal origin, which are often considered among the most frequently adulterated foods [ 3 , 4 , 5 , 6 ]. Market globalization and increases in international trade, driven by fewer obstacles to the export and import of food, a complex food production chain, and the complex nature of food products of animal origin, the huge variety of these products, as well as the emergence of tricky and more sophisticated forms of fraud are some of the reasons that could explain this rise in food fraud and why detection and prevention are challenging tasks [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%